PENGARUH MODEL PEMBELAJARAN COOPERATIVE TIPE STUDENT TEAM ACHIEVEMENT DIVISIONS BERBANTUAN QUIZIZZ TERHADAP KEMAMPUAN BERPIKIR KREATIF SISWA SEKOLAH DASAR - Salsabila, Nisrina Fairuz; Puji Rahayu; Hafiziani Eka Putri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The background of this research is based on the low level of mathematical creative thinking skills among elementary school students. One effort to improve this condition is by using the cooperative learning model of Student Team Achievement Divisions (STAD). The aim of this study is to determine the improvement and impact of the cooperative learning model of Student Team Achievement Divisions (STAD) assisted by Quizizz on the creative thinking abilities of fourth-grade students at SDN Cikarang Kota 02. The type of research conducted is a quasi-experiment. The design of this research is a non-equivalent control group design with pretest and posttest measures. The research sample consists of 20 students from class IV A and 20 students from class IV B. The instrument used in this research is a test. The results show that the improvement in mathematical creative thinking skills of students in class IV A, who were taught using the Student Team Achievement Divisions (STAD) cooperative learning model, was better compared to students in class IV B, who were taught using conventional methods. There is also an impact of applying the cooperative learning model of Student Team Achievement Divisions (STAD) on students' mathematical creative thinking abilities in elementary school, with an effect size of 76.7%. Based on these results, the cooperative learning model of Student Team Achievement Divisions (STAD) can be considered an alternative for use in the classroom to make learning more efficient, enjoyable, and meaningful.